Microbiological standards for food: what has changed in 18 years? - Silva, Allana Dayana de Souza Salvador da (2020)
Objective: This study aimed to show the main changes in the microbiological standards for food, occurred after the repeal of Resolution - RDC No. 12, of January 2, 2001, by Resolution - RDC No. 331, of December 23, 2019. Methods: A comparative study of RDC was performed to identify the modifications regarding food groups, the number of sample units to be collected, indication of the number of acceptable samples, types of microorganisms, and their tolerance limits. Results: The following main changes were observed: 1) inclusion of aerobic mesophiles and enterobacteria (hygienic indicators), Escherichia coli (fecal microorganism), Cronobacter spp. (for infant foods), and microbial toxins and metabolites; 2) increased demand for tolerance limits for some food groups; and 3) the creation of specific categories for certain food groups, such as poultry meat. Conclusion: RDC No. 331, of December 23, 2019, provided more security to consumers, as it is applied to foods ready for consumption, implying greater rigor in their production, especially those easily accessible to the population, with high nutritional content and intended for groups at risks such as infants and newborns.